Cold-paving type pavement anti-sliding finishing cover and construction method of cold-paving type pavement anti-sliding finishing cover

By optimizing materials and processes, high-performance modified emulsified asphalt, DMS anti-slip aggregate and high-viscosity adhesive, combined with cold mixing and cold paving technology, the problems of insufficient anti-slip performance, poor durability, and low construction efficiency in the existing pavement anti-slip treatment technology are solved, and efficient, low-carbon and multi-functional pavement maintenance effects are achieved.

CN120575459APending Publication Date: 2025-09-02GUANGZHOU FANGHUA TRANSPORTATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510843112.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

The existing anti-slip treatment technology of pavement has problems such as insufficient anti-slip performance, poor durability, limited adaptability to the construction environment, low construction efficiency, large material consumption, and single functionality. Especially in low-temperature environments, the construction is limited and the composite diseases such as ruts and pits cannot be effectively repaired.

Method used

High-performance modified emulsified asphalt, DMS anti-slip aggregate and high-viscosity adhesive are adopted, combined with the "touch first and then lay" cold mixing and cold laying process, optimize the aggregate grading, realize the normal temperature construction, improve the anti-slip performance and apparent quality, and reduce material consumption and construction costs.

Benefits of technology

It has achieved significant improvement in anti-slip performance, durability, apparent quality is close to the thermal paving effect, optimized driving comfort, strong low temperature adaptability, high construction efficiency, low cost, and multi-functional treatment capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a cold-paving type pavement anti-sliding finishing cover and a construction method, and belongs to the field of road engineering maintenance. The cover surface takes high-performance modified emulsified asphalt (the asphalt-aggregate ratio is 6.0-8.0%) as a cementing material, DMS anti-skid aggregate (the grading meets 100% of a 9.5 mm sieve, 90-100% of a 8.0 mm sieve and the like) as aggregate, a high-permeability and high-viscosity binder (the spreading amount is 0.2-0.4 kg / m) as a waterproof bonding layer, and 0.1-0.3% of fibers and 0-3% of cement are supplemented. The construction method comprises the construction steps of old pavement pretreatment, binder spreading, normal-temperature paving (the thickness is 6-10 mm, and the speed is 10-30 m / min) and curing for 1-2 hours to open traffic, and the construction temperature is larger than or equal to 5 DEG C. According to the technology, the pendulum friction coefficient reaches 70-80, ruts below 1.5 cm can be repaired, the unit price is 33-35 yuan / m < 2 >, the cost is half of that of traditional hot paving, and the technology is suitable for preventive maintenance of asphalt and cement pavements and is low-carbon, efficient, skid-resistant and durable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of road engineering maintenance, and in particular to a high-slip resistance road surface based on a cold-mix cold-paving process and a construction method thereof. Background Art

[0002] Among existing pavement anti-skid treatment technologies, traditional micro-surfacing processes (such as MS-3) and the "two oil and one sand" process have the following significant defects: 1. Limitations of the traditional MS-3 micro-surfacing process Insufficient anti-slip performance and poor durability The pendulum type friction coefficient (BPN) is usually 50-60. After a certain number of years of traffic, the lateral force coefficient (SFC) is likely to be lower than 40, which cannot meet the long-term anti-skid requirements; the proportion of fine aggregate in the mixture is relatively high, and the coarse aggregate is easily exposed and protruded, resulting in poor surface uniformity and insufficient flatness. The appearance effect is significantly different from that of the hot paving process.

[0003] Driving comfort and noise issues Uneven distribution of coarse material can easily cause driving noise, and excessive surface roughness affects smoothness.

[0004] Limited adaptability to the construction environment The construction temperature needs to be ≥10℃. In low temperature environments, emulsified asphalt demulsifies slowly, the curing time is extended, and construction in winter is restricted.

[0005] 2. Defects of the “Two Oils and One Sand” Process Low construction efficiency, high material consumption and high cost The adhesive and sand need to be spread in multiple layers. The daily construction volume of a single lane is low, and the paving thickness is usually ≥15mm. The amount of stone and asphalt used is large, and the cost is high. In a low temperature environment, the adhesive is easily picked up by the wheels, resulting in failure of the interlayer bond, and additional curing time is required.

[0006] Single functionality It can only solve the anti-skid problem, but cannot repair complex defects such as ruts (depth ≤ 15mm) and potholes, and needs to be treated in conjunction with other processes.

[0007] 3. Technical Breakthrough Direction of the Invention In view of the above-mentioned defects, the present invention achieves technical upgrades through the following improvements: Material system optimization: High-performance modified emulsified asphalt and high-permeability and high-viscosity adhesives are used. The former has fast-setting properties and excellent adhesion, while the latter has rapid surface drying and high bonding strength.

[0008] Grading innovation: optimize aggregate grading, reduce the proportion of fine aggregate, increase the proportion of coarse aggregate, enhance the strength of the skeleton embedded structure, and achieve a dual improvement in anti-slip performance and surface quality.

[0009] Technological innovation: Adopting the "stick first, then lay" cold mix and cold laying process, the construction temperature is widened to ≥5℃, the curing time is shortened to 1-2 hours, and the material consumption is reduced. It has both high efficiency, low carbon and multi-functional treatment (anti-skid, rutting repair, flatness improvement) capabilities. Summary of the Invention

[0010] The present invention aims to provide a cold-laid pavement anti-skid finish and construction method. This invention addresses the shortcomings of existing processes in terms of anti-skid durability, construction efficiency, low-temperature adaptability, and high resource consumption. The present invention achieves performance improvements through the following technological breakthroughs: Enhanced anti-slip performance: Optimize aggregate gradation and binder properties to increase BPN to 70-80 and maintain SFC ≥40 for 4-6 years; Innovation in construction technology: Adopting the "high-permeability and high-viscosity binder + cold-laid slurry mixture" process, it achieves normal temperature construction and improves efficiency by 30% compared with the "two oil and one sand" method. Adaptability to low temperature environments: The construction temperature is extended to ≥5°C, and construction is possible throughout the year in South China; Low carbon and environmentally friendly: thickness is reduced to 6-10mm, material consumption is reduced by 30%, unit price is 33-35 yuan / m², and the cost is 50% of the traditional hot laying process.

[0011] In order to achieve the above object, the present invention is implemented through the following technical solution: a cold-laid anti-skid fine surface for road surface, composed of the following materials: High-performance modified emulsified asphalt is used as the binder, with an oil-to-stone ratio of 6.0-8.0%, an evaporation residue softening point ≥ 65°C, and an elongation of ≥ 30cm at 5°C; DMS anti-slip aggregate as aggregate, including coarse aggregate with a nominal maximum particle size of ≤8mm and specially made highly reactive 0-3mm machine-made sand; High-permeability and high-viscosity adhesive is used as the waterproof bonding layer, with a spreading rate of 0.2-0.4kg / m², a surface drying time of ≤1 hour, and a tensile strength of ≥1.2MPa; Fiber 0.1-0.3% and cement 0-3% are used as additives.

[0012] As a further improvement to the technical solution of the present invention, the DMS anti-slip aggregate gradation satisfies: The passing rate of 9.5mm sieve is 100%, the passing rate of 8.0mm sieve is 90-100%, the passing rate of 4.75mm sieve is 30-100%, the passing rate of 2.36mm sieve is 20-50%, and the passing rate of 0.075mm sieve is 3-13%.

[0013] As a further improvement of the technical solution of the present invention, the high-permeability and high-viscosity adhesive is a solvent-based low-viscosity black liquid containing a polymer elastomer and a tackifying resin, with a rotational viscosity of 25°C ≤ 100 mPa·s, an evaporation residue softening point ≥ 85°C, and a needle penetration of 10-300.1 mm at 25°C.

[0014] As a further improvement to the technical solution of the present invention, the performance indicators of the anti-slip fine cover after molding meet the following requirements: The pendulum friction coefficient BPN ≥ 70, and BPN ≥ 65 one year after opening to traffic; Transverse force coefficient SFC ≥ 54, structural depth TD ≥ 0.6mm; Water permeability coefficient ≤120ml / min, wet wheel abrasion value 6d ≤800g / m².

[0015] As a further improvement of the technical solution of the present invention, the fiber is glass fiber, has an alkali metal oxide content of ≤0.8%, a breaking strength of ≥0.25N / tex, and needs to be evenly dispersed in the mixture without agglomeration.

[0016] As a further improvement to the technical solution of the present invention, the cement is 32.5 or 42.5 grade Portland cement.

[0017] As a further improvement of the technical solution of the present invention, the surface quality requirements of the anti-slip fine cover are: the surface is flat and dense, without exposed protrusions of coarse materials, the flatness is ≤3mm, and the driving noise is ≤70dB, which is close to the effect of hot-laid ultra-thin cover.

[0018] As a further improvement to the technical solution of the present invention, a construction method for a cold-laid pavement anti-skid finish comprises the following steps: Pretreatment: If the width of cracks on old pavement is ≤5mm, they should be treated directly; if the width of cracks on old pavement is ≥5mm, they should be filled; if the depth of ruts is ≤15mm, they should be covered directly; if the depth of ruts is >15mm, they should be filled first; if there are gaps in cement pavement, grouting and fine milling should be used for leveling; Spread the adhesive layer: Use a special spreading vehicle to evenly spray the high-permeability and high-viscosity adhesive, and cure it until the wheel does not stick for ≤1 hour; Paving mixture: Slurry sealer mixes aggregate, emulsified asphalt, water, cement, and fiber at room temperature, with a paving thickness of 6-10mm and a speed of 10-30m / min; Health preservation opening: Traffic will be opened after 1-2 hours of health preservation. When the temperature is ≥5℃, the health preservation time will be extended to 2 hours.

[0019] As a further improvement to the technical solution of the present invention, the construction temperature control satisfies: the paving temperature ≥ 5°C, and the air temperature during the curing period ≥ 10°C.

[0020] As a further improvement to the technical solution of the present invention, the rubber wheel rolling process is as follows: After curing for 30-60 minutes, use a rubber-wheel roller to roll the road surface 2-3 times at a speed of 1.5-2.0 km / h, starting from the sides and then the middle.

[0021] The beneficial effects of the present invention are as follows: Anti-slip performance is significantly improved and lasting: The pendulum friction coefficient (BPN) has been increased from 50-60 in traditional technology to over 70-80, and can still be maintained at ≥65 one year after opening to traffic; the lateral force coefficient (SFC) is ≥54, which can ensure that the anti-skid performance is not lower than the standard requirements within 4-6 years.

[0022] The apparent quality is close to the hot-laying effect: The coarse aggregate is evenly distributed and dense, with no exposed protrusions, the surface flatness is ≤3mm (3m ruler detection), the appearance color is uniform, the effect is close to that of hot-laid ultra-thin covering, and there is no floating sand or falling particles.

[0023] Driving comfort and noise control optimization: Driving noise is significantly reduced, approaching the level of the "two oils and one sand" process. The surface is rough and uniform, without scratches and loose particles, improving driving smoothness.

[0024] Low temperature construction adaptability and environmental protection advantages: The lowest construction temperature can be as low as 5°C, which broadens the construction temperature range and is applicable throughout the year in South China. The normal temperature cold mixing and cold laying process is adopted, which reduces energy consumption by more than 50%, material consumption by 30%, and the thickness is only 6-10mm.

[0025] Highly efficient, economical and multifunctional treatment: The construction efficiency is 30% higher than that of the "two oil and one sand" process, and the daily construction volume of a single lane can reach 2,000-3,000 square meters; the unit price is 33-35 yuan / square meter, and the cost is only 50% of the traditional hot paving process; it can simultaneously achieve anti-skid treatment, repair ruts below 1.5 cm, fill potholes and cracks, and improve flatness and other multifunctional maintenance.

[0026] Enhanced interlayer bonding and durability: High-permeability and high-viscosity adhesives ensure strong interlayer bonding and significantly improve pull-out strength; the mixture cohesion (60min) is ≥2.0N·m, the wet wheel abrasion value (6d) is ≤800g / m², and it has excellent crack resistance and water stability. The durability of the cement bridge deck remains intact 16 months after it was opened to traffic. DETAILED DESCRIPTION

[0027] The present invention will be described in detail below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0028] A cold-laid anti-skid fine overlay for road surface, comprising the following materials: High-performance modified emulsified asphalt is used as the binder, with an oil-to-stone ratio of 6.0-8.0%, an evaporation residue softening point ≥ 65°C, and an elongation of ≥ 30cm at 5°C; DMS anti-slip aggregate as aggregate, including coarse aggregate with a nominal maximum particle size of ≤8mm and specially made highly reactive 0-3mm machine-made sand; High-permeability and high-viscosity adhesive is used as the waterproof bonding layer, with a spreading rate of 0.2-0.4kg / m², a surface drying time of ≤1 hour, and a tensile strength of ≥1.2MPa; Fiber 0.1-0.3% and cement 0-3% are used as additives.

[0029] Specifically, in this embodiment, the gradation of the DMS anti-slip aggregate satisfies: The passing rate of 9.5mm sieve is 100%, the passing rate of 8.0mm sieve is 90-100%, the passing rate of 4.75mm sieve is 30-100%, the passing rate of 2.36mm sieve is 20-50%, and the passing rate of 0.075mm sieve is 3-13%.

[0030] Specifically, in this embodiment, the high-permeability and high-viscosity adhesive is a solvent-based low-viscosity black liquid containing a polymer elastomer and a tackifying resin, with a rotational viscosity of 25°C ≤ 100 mPa·s, an evaporation residue softening point ≥ 85°C, and a needle penetration of 10-300.1 mm at 25°C.

[0031] Specifically, in this embodiment, the performance indicators of the anti-slip fine cover after molding meet the following requirements: The pendulum friction coefficient BPN ≥ 70, and BPN ≥ 65 one year after opening to traffic; Transverse force coefficient SFC ≥ 54, structural depth TD ≥ 0.6mm; Water permeability coefficient ≤120ml / min, wet wheel abrasion value 6d ≤800g / m².

[0032] Specifically, in this embodiment, the fiber is glass fiber, has an alkali metal oxide content of ≤0.8%, and a breaking strength of ≥0.25N / tex, and needs to be evenly dispersed in the mixture without agglomeration.

[0033] Specifically, in this embodiment, the cement is 32.5 or 42.5 grade Portland cement.

[0034] Specifically, in this embodiment, the surface quality requirements of the anti-slip fine cover are: the surface is flat and dense, without exposed rough materials and protrusions, the flatness is ≤3mm, and the driving noise is ≤70dB, which is close to the effect of hot-laid ultra-thin cover.

[0035] Specifically, in this embodiment, a method for constructing a cold-laid anti-skid finish on a pavement includes the following steps: Pretreatment: If the width of cracks on old pavement is ≤5mm, they should be treated directly; if the width of cracks on old pavement is ≥5mm, they should be filled; if the depth of ruts is ≤15mm, they should be covered directly; if the depth of ruts is >15mm, they should be filled first; if there are gaps in cement pavement, grouting and fine milling should be used for leveling; Spread the adhesive layer: Use a special spreading vehicle to evenly spray the high-permeability and high-viscosity adhesive, and cure it until the wheel does not stick for ≤1 hour; Paving mixture: Slurry sealer mixes aggregate, emulsified asphalt, water, cement, and fiber at room temperature, with a paving thickness of 6-10mm and a speed of 10-30m / min; Health preservation opening: Traffic will be opened after 1-2 hours of health preservation. When the temperature is ≥5℃, the health preservation time will be extended to 2 hours.

[0036] Specifically, in this embodiment, the construction temperature is controlled to meet the following requirements: paving temperature ≥ 5°C, and air temperature during the curing period ≥ 10°C.

[0037] Specifically, in this embodiment, the rubber wheel rolling process is: After curing for 30-60 minutes, use a rubber-wheel roller to roll the road surface 2-3 times at a speed of 1.5-2.0 km / h, starting from the sides and then the middle.

[0038] It should be noted that the technical requirements for raw materials of a cold-laid anti-skid fine overlay are as follows: Raw material technical requirements Technical requirements for aggregates The aggregate used for DMS anti-skid fine overlay must be a special DMS anti-skid aggregate produced through standardized technology using hard, wear-resistant, alkaline stones such as basalt or diabase. The specific quality and technical requirements are shown in the "DMS Anti-skid Aggregate Quality Technical Requirements".

[0039] DMS anti-skid aggregate quality technical requirements

[0040] Aggregate gradation requirements The gradation of DMS anti-skid aggregate should meet the "DMS anti-skid aggregate gradation range". During the construction process, each batch of anti-skid aggregate shipped from the factory to the site must be sampled and screened. When the test value exceeds the adopted gradation range, it should be abandoned.

[0041] DMS anti-slip aggregate gradation range model Sieve hole size (mm) 9.5 8.0 4.75 2.36 1.18 0.6 0.3 0.15 0.075 DMS Pass rate (%) 100 90-100 30-100 20-50 15-40 10-31 6-23 4-17 3-13 Technical requirements for high performance modified emulsified asphalt

[0042] The binder of DMS anti-skid finishing mixture adopts special high-performance modified emulsified asphalt. The specific technical requirements of the emulsion can be found in the "Technical Requirements for High-Performance Modified Emulsified Asphalt".

[0043] Technical requirements for high-performance modified emulsified asphalt

[0044] Note: The factory inspection of storage stability must meet the technical requirements, but no such requirements are required for on-site inspection. The asphalt must be circulated or stirred before use. Technical requirements for high-permeability and high-viscosity adhesives

[0045] Before spreading the slurry mixture, a layer of tack oil should be spread on the DMS anti-skid fine surface to enhance inter-layer adhesion and waterproofing. The tack oil should be made of a special oily non-stick wheel high-permeability and high-viscosity adhesive. Spreading must be done with a special mechanized oily asphalt spreader. Half an hour after spreading, it can achieve the effect of not being damaged by paving and construction wheels. It has excellent bonding and waterproofing properties. The spreading amount is 0.2-0.4kg / square meter. For specific technical requirements, see "Technical Requirements for High-Permeability and High-Viscosity Adhesives".

[0046] Technical requirements for high-permeability and high-viscosity adhesives Technical requirements of fibers

[0047] Fiber plays a crucial role in slurry mixtures. Adding an appropriate amount of fiber (0.1-0.2%) can improve the cohesion and toughness of DMS high-viscosity fiber anti-skid finish mixtures. Therefore, if conditions permit, glass fiber for road construction can be added. However, sufficient fiber dispersion must be ensured, ensuring uniform distribution throughout the mixture. Fiber dispersion should be verified in the laboratory during the mix design phase, and fiber clumping must be avoided.

[0048] Fibers should be stored indoors or under a covered roof to prevent moisture and clumping. Fibers that are damp, clumped, and unable to disperse properly during mixing should not be used. Fiber use must comply with environmental protection requirements and pose no health risks. Asbestos fibers that are likely to impact the environment or cause harm to the human body should not be used. Specific technical requirements for glass fiber are as follows.

[0049] Glass fiber technical requirements project index Test methods Appearance There should be no stains that affect use, the color should be uniform, the yarn bobbin should be tightly and regularly wound into a cylindrical shape to ensure easy unwinding. JT / T278 Alkali metal oxide content ≤0.8% JT / T278 Line density 150~9600tex JT / T278 Breaking strength ≥0.25N / tex JT / T278 Moisture content ≤0.2% GB11966 drape ≤50mm GB11966 Slurry mixture design and requirements

[0050] The design of slurry mixture for DMS anti-skid overlay should fully consider factors such as original road conditions, traffic volume, climatic conditions, etc., select appropriate DMS anti-skid overlay raw materials and proportions, and determine the formula of the slurry mixture through slurry mixture proportion tests.

[0051] The paving thickness of DMS anti-skid fine overlay is 6-10mm. It is suitable for preventive maintenance, anti-skid treatment, rut repair and medium repair overlay on asphalt pavement. It is also suitable for "white to black" thin layer overlay on cement concrete pavement or bridge deck. The material usage range is shown in "Usual Material Usage Range of DMS Anti-skid Fine Overlay".

[0052] Typical material usage range for DMS anti-slip finish project Material usage Thickness after curing (mm) 6~10 Mineral material consumption (kg / m2) 14~22 Asphalt-to-rock ratio (mass percentage of asphalt in mineral aggregate)% 6.0~8.0 Cement content (mass percentage of aggregate) % 0~3 Amount of added water (mass percentage of mineral material) % Determined by the consistency of the mixture Fiber content (mass percentage of mineral material)% 0.1~0.3 The technical requirements for the performance of DMS anti-slip fine coating are shown in the table "Technical Requirements for DMS Anti-slip Fine Coating".

[0053] Technical requirements for DMS anti-slip finish.

[0054] Example: A construction method for a cold-laid pavement anti-skid fine surface finish comprises the following steps: Carry out the following preparations before construction (1) The original road surface should be pre-treated before construction. Common road surface damage repair; formulate effective treatment measures based on the characteristics and causes of different damages, eliminate quality risks in a timely manner and prevent the expansion of the disease, so as to ensure the quality and service life of the road surface.

[0055] (2) Before construction, all types of machinery used for construction should be thoroughly inspected and debugged to ensure that they are in good condition before construction can begin. Spare parts for important machinery and equipment should also be kept. Usually, the measurement control system of the machinery should be calibrated in the following three situations: first, before the machinery is used for the first time after entering the site; second, the machinery should be calibrated every six months during continuous production; third, when there is a significant change in the raw material ratio, the calibration method should refer to the manufacturer's product manual.

[0056] (3) Construction is not allowed when the temperature is below 5℃; construction is not allowed when the temperature reaches 5℃ and keeps falling; construction is allowed when the temperature reaches 5℃ and keeps rising; construction is not allowed before the road surface water has dried or been cleared after rain; construction is not allowed during the construction and maintenance period if there may be rainfall; the temperature must be greater than 10℃ during the maintenance period.

[0057] The construction is carried out in the following steps: (1) Close the traffic on the construction section first: Contact the traffic management department of the section before construction and jointly develop a traffic control coordination plan to ensure sufficient maintenance time after construction. Take appropriate measures to minimize the impact of construction on traffic as much as possible, and set up sufficient construction safety signs according to the traffic diversion plan and safety regulations.

[0058] (2) Cleaning of the road surface in the construction section: First, organize cleaning personnel to clean the closed construction section, remove all debris and dirt on the road surface, and blow it clean with a hair dryer. For mud cakes stuck on the original road surface, first use a shovel to remove them, and then use a steel brush to brush them repeatedly. For areas on the original road surface that are contaminated by grease, first use a detergent and then rinse with water. The cleaned road surface should be dry, clean, free of dust, water accumulation, and pollution. After cleaning, the road surface is strictly closed to traffic, and pedestrians and vehicles are prohibited from walking on it to ensure the quality of construction.

[0059] (3) Spreading adhesive layer: Spread a layer of high-permeability and high-viscosity adhesive before paving, with a dosage of 0.2-0.4kg / m 2 The material cannot be diluted during the construction process. It must be cured for half an hour after spreading to achieve the non-stick wheel effect to prevent the adhesive layer material from being damaged by the paving and construction wheels before the next paving step can be carried out.

[0060] (4) DMS anti-skid finish paving construction a. Drive the loaded paver to the construction starting point, align it with the direction control line, and adjust the paving thickness and crown of the paving box so that the periphery of the paving box is tightly adhered to the original road surface.

[0061] b. Adjust the height or opening of each material door according to the production mix ratio and the moisture content of the on-site mineral materials.

[0062] c. Start the engine, engage the mixing cylinder clutch, make the agitator shaft run normally, and start the paving box spiral distributor.

[0063] d. Open the control switches of each material door to allow aggregate, cement and water to enter the mixing tank at the same time. When the pre-wetted mixture is spread to the emulsion spray outlet, the emulsion will be sprayed out.

[0064] e. Adjust the flow direction of the slurry on the distributor so that the slurry can flow evenly to the left and right of the paving box.

[0065] f. Adjust the amount of water to make the slurry have moderate consistency and strictly control the amount of added water.

[0066] g. When the slurry mixture is evenly distributed across the entire width of the paving box, the operator notifies the driver to start the sealing vehicle and move forward slowly. The forward speed is generally 10-30 m / min, but the slurry paving volume should be kept basically consistent with the production volume, and the volume of the slurry mixture in the paving box should be kept at about 1 / 2 of the paving box volume.

[0067] h. When any material on the paver is used up, all material delivery control switches should be turned off immediately to allow the mixture in the mixing tank to be evenly mixed and sent into the paving box. After paving, notify the driver to stop.

[0068] i. Lift the paving box, drive the paver and paving box off the road, and clean the mixing tank and paving box.

[0069] j. Check the remaining amount of materials.

[0070] (5) Repair and trimming After the mixture is spread, local construction defects should be repaired manually immediately. The focus of the repair is on the starting point, end point, longitudinal joints, and areas of excessive thickness, thinness, or unevenness. In particular, longitudinal scratches caused by oversized stone should be removed and filled as soon as possible. After repair, the surface should be flat, the edges should be straight, and the joints should be smooth.

[0071] (6) Rubber wheel rolling For projects with low traffic volume, long construction sections, or other reasons where the slurry mixture requires prolonged curing, rubber tires can be used for immediate follow-up rolling, as it is not possible to achieve a good compaction effect by immediately opening the road to traffic. Once the slurry mixture has cured to a certain strength (generally 30-60 minutes) and the rubber-tire roller can drive over it without being dragged away, rolling can begin. Typically, two to three passes are made, rolling the mixture at a slow, uniform speed, following the principle of first rolling the edges and then the center.

[0072] (7) Initial maintenance and opening to traffic During the initial maintenance phase of the DMS anti-skid coating, no personnel or vehicles are allowed to walk on the DMS anti-skid coating until the DMS anti-skid coating has solidified and formed, meeting the conditions for opening to traffic.

[0073] 7.2 Construction Quality Management and Control Standards 7.2.1 Quality Control of DMS Anti-Slip Finish Raw Materials (1) Aggregate. The aggregate must be a special DMS anti-skid aggregate produced by standardized technology using hard, wear-resistant, alkaline stones such as basalt or diabase. Its quality must meet the "Technical Requirements for DMS Anti-skid Aggregate Quality". The aggregate gradation must meet the "DMS Anti-skid Aggregate Grading Range". During the construction process, each batch of DMS anti-skid aggregate delivered to the site must be sampled and screened. When the test value exceeds the adopted grading range, it should be discarded. Attention should be paid to the stacking of aggregates after construction. Aggregates should be stacked on clean ground as much as possible to avoid mixing with soil during loading and unloading.

[0074] (2) Water. Ordinary drinking water can be used. The water does not contain harmful substances such as soluble salts. Industrial wastewater must not be used. The amount of water used can be determined by consistency testing. Generally, the water content in the mixture is controlled within the range of 3% to 6%.

[0075] (3) Asphalt. The modified emulsified asphalt used in the mixture binder should be a high-performance modified emulsified asphalt specially designed for DMS anti-skid topcoat. The technical indicators of the emulsion should meet the "Technical Requirements for High-Performance Modified Emulsified Asphalt". The emulsion's demulsification and forming speed should be slow cracking and fast setting. The key indicators of evaporation residue are softening point ≥ 65°C and elongation at 5°C ≥ 30cm. Other indicators should meet the technical requirements of the BCR type modified emulsified asphalt. The tack coat oil asphalt used in the waterproof bonding layer should be a high-permeability and high-viscosity adhesive specially designed for DMS anti-skid topcoat. In addition to having excellent bonding and waterproofing properties, the most important feature of the tack coat oil is that it can resist being damaged by paving and construction wheels within half an hour after being spread.

[0076] (4) Cement: Ordinary or composite silicate 32.5 or 42.5 cement is used.

[0077] (5) Additives. The added additives ensure that the DMS anti-skid coating reaches the required demulsification speed.

[0078] (6) Fiber. Fiber can be added as glass fiber for road engineering.

[0079] Construction quality control of DMS anti-skid fine finish a. Test reports of construction materials can only be used after they are confirmed to meet the requirements of the specifications.

[0080] b. Before construction, a test report of the mixture must be provided. Construction can only be carried out after changes are found and meet the requirements. When the evaporation residue content of the emulsified asphalt and the water content of the mineral aggregate change, the mix ratio should be adjusted to meet the requirements and construction should be carried out according to the adjusted mix ratio.

[0081] c. During construction, sampling inspection should be carried out on the performance of DMS anti-skid fine coating, and the performance inspection requirements of DMS anti-skid fine coating should be met.

[0082] d. Consistency control. The DMS anti-skid fine overlay should maintain the required consistency and stability after entering the paving box. If the slurry mixture is too viscous, it will easily break down prematurely in the paving box. If the fluidity of the slurry mixture is too poor, it will affect the flatness of the paving layer and leave scratches under the action of the scraper. If the slurry mixture is too thin, it will segregate. Fine particles containing a large amount of asphalt will float on the surface, affecting the friction coefficient of the road surface and causing oil overflow, which will also affect the adhesion with the original road surface. If the slurry mixture is too fluid, it will flow to depressions and cause uneven thick and thin paving layers. Therefore, appropriate adjustments to the water consumption should be made on site according to actual conditions to ensure the appropriate construction consistency of the slurry mixture.

[0083] e. Thickness Control. Each batch of incoming raw materials is rigorously inspected. The amount of mixture determines the thickness of the paving layer, which is typically determined by the aggregate gradation. Paving that is too thin or too thick will affect construction quality. During construction, the operator must promptly adjust the paving thickness to avoid excessive thickness, resulting in shiny, oily surfaces. During the paving process, the thickness should be promptly inspected and controlled, with each lane inspected every 100 meters, left, center, and right, to ensure that the paving thickness is achieved and that the final thickness meets the design requirements.

[0084] f. Aggregate gradation control: Strictly follow the aggregate gradation range requirements in the DMS Anti-slip Aggregate Grading Range to control the gradation of each batch of aggregate entering the site. Aggregates that do not meet the requirements should be discarded.

[0085] g. Demulsification time control. The slurry mixture should maintain the necessary construction stability during mixing and paving to prevent premature reagglomeration of asphalt particles in the emulsified asphalt. Demulsification time can be controlled by adjusting the water volume, slightly adjusting the cement dosage, or adding appropriate amounts of chemical additives.

[0086] h. Construction temperature control: The paving temperature of the DMS anti-skid finish should be controlled above 5°C, and the curing temperature should be controlled above 10°C.

[0087] i. Construction appearance quality control shall meet the following requirements: ⑴The surface is flat, dense, without looseness or wheel marks.

[0088] ⑵ The longitudinal and transverse seams are smoothly connected and the appearance color is uniform.

[0089] ⑶ The connection with other structures is smooth and pollution-free.

[0090] ⑷ There is no slurry mixture flowing out of the paving range.

[0091] ⑸The surface is rough and there is no oil spillage.

[0092] j. Control of traffic opening hours. Pedestrians and vehicles should be prohibited from entering the road before the mixture reaches initial solidification. In particular, after initial setting, the mixture still requires a period of curing before it gradually hardens to a point where it can support vehicle movement. Therefore, the traffic opening hours should be longer than the initial setting time. During this period, vehicles should be prohibited from passing to avoid leaving wheel marks. The traffic opening hours will be determined based on site conditions such as temperature, humidity, and wind speed.

[0093] Precautions for construction of DMS anti-skid finish a. When paving, you must strictly follow the mix ratio requirements and accurately add various materials required by the design.

[0094] b. Aggregates stored at the material plant should not be piled too high, but should be around 1.5 meters high. Water should be sprayed appropriately to maintain a certain moisture content in the aggregates to avoid segregation, which would affect the paving effect. The loader should also turn the aggregates back and forth during loading to ensure uniformity.

[0095] c. Keep the mouth of the emulsified asphalt storage tank sealed as much as possible, or try not to damage the surface crust during loading and unloading to prevent more crusts from forming.

[0096] d. When paving, the operator must understand the characteristics and be skilled in operation, reasonably and correctly judge the water consumption, and try to achieve consistent paving results for each vehicle.

[0097] e. Records are the most important basis for summarizing experience and analyzing problems, so they must be filled out carefully and meticulously for each vehicle according to the requirements of the construction record form.

[0098] f. The paving trough operator must control the paving thickness. It should not be too thin to cause scratches or too thick to affect the effect. The longitudinal joints should be flat and straight. When dealing with transverse joints, excess material should be scraped off to ensure its flatness. Transverse joints and paving defects should be promptly addressed to ensure a smooth and beautiful paving.

[0099] g. Each position must clearly define responsibilities and diligently adhere to the division of labor and cooperation. Each work area manager must research, analyze, and master paving technology, rationally arrange work, and consider every detail, including equipment maintenance and adjustments, material inventory, construction sections, safety facilities, road conditions, weather information, paving time, longitudinal and transverse joint treatment, emulsion breaking time, rolling time, traffic opening, material usage, and worker performance.

[0100] Construction process quality inspection (1) Appearance quality requirements of DMS anti-skid fine coating: After construction is completed, the pavement surface should be flat, dense, without looseness and wheel marks; the longitudinal and transverse joints should be smoothly connected, and the appearance color should be uniform; the connection with other structures should be smooth and pollution-free; there should be no slurry mixture flowing out of the paving range; the surface should be rough and without oil spillage.

[0101] (2) Raw materials and mixtures should be sampled and tested in a timely manner during the construction process. The sampling items, frequency, requirements and inspection methods are shown in the "Inspection Requirements during the Construction Process".

[0102] Construction process inspection requirements project Require Inspection frequency Inspection methods Aggregate quality Meet the "DMS Anti-slip Aggregate Quality Technical Requirements" 1 batch / 200t See table "DMS Anti-slip Aggregate Quality Technical Requirements" Modified emulsified asphalt Meet the "Technical Requirements for High-Performance Modified Emulsified Asphalt" 1 batch / 60t See the table "Technical Requirements for High-Performance Modified Emulsified Asphalt" Mineral coating >2 / 3 1 time / each vehicle Visual inspection consistency Moderate 1 time / 100m empirical method Oil-stone ratio ±0.5% (single) ±0.2% (daily average) 1 time / day Extraction calculation method Cement usage ±1% 1 time / day Calculation method Fiber dosage ±1% 1 time / day Calculation method Paving volume ±1kg / m2 1 time / day Calculation method Paving thickness 6~10mm 5 sections / km Use a steel ruler or other effective means to measure every 1 point in the middle and on both sides, and take the average value as the test result. Aggregate gradation Meet the "DMS Anti-slip Aggregate Grading Range" 1 time / day During the paving process, the aggregate is taken from the end of the mineral conveyor belt for screening Appearance Smooth, dense, uniform, no loose, no white material, no wheel marks, no scratches, smooth seams Full line continuous Visual inspection Wet wheel wear after 1h immersion in water Not more than 540g / m2 1 time / 7 working days JTJ058-2000(T0752-1993) Note: The oil-stone ratio shall be tested at least once a day and determined by the mixture extraction method or the counter reading on the paver. The amount of cement used is allowed to vary by ±1% and is determined by the corresponding counter reading on the paver. The paving amount is determined by the daily paving area corresponding to the paver counter reading. Completion acceptance inspection requirements

[0103] One to three months after the project is completed and opened to traffic, the road surface performance and apparent quality inspection and acceptance will be carried out on the entire construction line with 1km to 3km as an evaluation section. The inspection items, frequency, requirements and methods are shown in the "Road Surface Performance and Apparent Quality Acceptance Inspection Requirements". In winter, the construction road surface temperature is lower and the water permeability coefficient can be extended to 4-6 months later.

[0104] Road surface performance and apparent quality acceptance inspection requirements

[0105] Note: According to the site conditions, one of the test items of swing value Fb (BPN) and lateral force coefficient SFC can be selected as the acceptance index of anti-skid performance.

[0106] Project Case 1: Northbound Test Road of a Certain Expressway Project Overview: The road section is asphalt pavement with a length of 450 meters and a paving thickness of 7mm.

[0107] Material parameters: Aggregate gradation: 8mm sieve pass rate 95%, 4.75mm sieve 50%, 2.36mm sieve 30%, 0.075mm sieve 8%; The oil-stone ratio is 7.0%, the cement content is 2%, and the glass fiber content is 0.2%; The spreading amount of high-permeability and high-viscosity adhesive is 0.3kg / m² and the surface drying time is 45 minutes.

[0108] Construction steps: The original road surface with slight rutting (depth ≤ 15mm) is directly covered, and after removing debris, fine milling is done to 1cm; Use a special spreading vehicle to evenly spray the adhesive and allow it to cure for 1 hour until the wheels are no longer sticky; The slurry sealer is paving at a speed of 20m / min, and the volume of the mixture in the paving box is kept at 1 / 2 volume; The construction temperature is 10℃ and traffic will be opened after curing for 1.5 hours.

[0109] Test data: One month after opening to traffic: structural depth 0.9mm, pendulum value 73BPN, water seepage coefficient 35ml / min; 1 year after opening to traffic: structural depth 0.85mm, swing value 65BPN, water seepage coefficient 30ml / min.

[0110] Project Case 2: Test Road of a Highway Bridge Section Project Overview: The road section is cement + asphalt pavement, with a length of 500 meters and a paving thickness of 6mm.

[0111] Material parameters: Use 3-5mm coarse aggregate, 6.5% oil-stone ratio, and 1% cement content.

[0112] Test data: 1 year after opening to traffic: lateral force coefficient (SFC) 55, meeting the long-term anti-skid design requirements.

[0113] Project Case 3: Asphalt Pavement Test Road in a Highway Tunnel Project Overview: Single lane tunnel construction, total length 1460 meters (including multiple tunnels), paving thickness 6mm.

[0114] Construction features: One lane is closed for construction and will be reopened to traffic after 1 hour of maintenance. Traffic will not be affected. The construction temperature was 8°C, and the mixture demulsified and formed normally without problems of wheel sticking or delayed curing.

[0115] Test data: 1 week after opening to traffic: structural depth 0.8mm, pendulum value 80BPN, water seepage coefficient 87ml / min; 3 months after opening to traffic: structural depth 0.86mm, swing value 73BPN, water seepage coefficient 56ml / min.

[0116] Project Case 4: Test Road of a Highway Roadbed Section Project Overview: The road section is asphalt pavement with a length of 1,000 meters and a paving thickness of 7mm.

[0117] Construction control: Aggregate gradation strictly complies with design requirements, with the daily average deviation of asphalt-aggregate ratio ≤±0.2%; The paving speed was maintained at 15m / min, and the thickness was tested at 3 points every 100 meters with an error of ±1mm.

[0118] Test data: 3 months after opening to traffic: structural depth 0.85mm, swing value 72BPN, meeting the anti-slip performance standards.

[0119] In summary, the specific beneficial effects of the present invention are as follows: Anti-slip performance is significantly improved and lasting: The pendulum friction coefficient (BPN) has been increased from 50-60 in traditional technology to over 70-80, and can still be maintained at ≥65 one year after opening to traffic; the lateral force coefficient (SFC) is ≥54, which can ensure that the anti-skid performance is not lower than the standard requirements within 4-6 years.

[0120] The apparent quality is close to the hot-laying effect: The coarse aggregate is evenly distributed and dense, with no exposed protrusions, the surface flatness is ≤3mm (3m ruler detection), the appearance color is uniform, the effect is close to that of hot-laid ultra-thin covering, and there is no floating sand or falling particles.

[0121] Driving comfort and noise control optimization: Driving noise is significantly reduced, approaching the level of the "two oils and one sand" process. The surface is rough and uniform, without scratches and loose particles, improving driving smoothness.

[0122] Low temperature construction adaptability and environmental protection advantages: The lowest construction temperature can be as low as 5°C, which broadens the construction temperature range and is applicable throughout the year in South China. The normal temperature cold mixing and cold laying process is adopted, which reduces energy consumption by more than 50%, material consumption by 30%, and the thickness is only 6-10mm.

[0123] Highly efficient, economical and multifunctional treatment: The construction efficiency is 30% higher than that of the "two oil and one sand" process, and the daily construction volume of a single lane can reach 2,000-3,000 square meters; the unit price is 33-35 yuan / square meter, and the cost is only 50% of the traditional hot paving process; it can simultaneously achieve anti-skid treatment, repair ruts below 1.5 cm, fill potholes and cracks, and improve flatness and other multifunctional maintenance.

[0124] Enhanced interlayer bonding and durability: High-permeability and high-viscosity adhesives ensure strong interlayer bonding and significantly improve pull-out strength; the mixture cohesion (60min) is ≥2.0N·m, the wet wheel abrasion value (6d) is ≤800g / m², and it has excellent crack resistance and water stability. The durability of the cement bridge deck remains intact 16 months after it was opened to traffic.

[0125] The technical solutions provided by the embodiments of the present invention are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the embodiments of the present invention. The description of the above embodiments is only applicable to help understand the principles of the embodiments of the present invention. At the same time, for those skilled in the art, according to the embodiments of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the contents of this specification should not be understood as limiting the present invention.

Claims

1. A cold-paved road anti-skid finish, characterized in that: It is composed of the following materials: High-performance modified emulsified asphalt is used as the binder, with an oil-to-stone ratio of 6.0-8.0%, an evaporation residue softening point ≥ 65°C, and an elongation of ≥ 30cm at 5°C; DMS anti-slip aggregate is used as aggregate, including coarse aggregate with a nominal maximum particle size of ≤8mm and specially made highly active 0-3mm machine-made sand; High-permeability and high-viscosity adhesive is used as the waterproof bonding layer, with a spreading amount of 0.2-0.4kg / m², surface drying time ≤ 1 hour, and tensile strength ≥ 1.2MPa; Fiber 0.1-0.3% and cement 0-3% are used as additives.

2. The anti-skid finish for cold-laid pavement according to claim 1, characterized in that: The DMS anti-skid aggregate gradation meets the following requirements: The passing rate of 9.5mm sieve is 100%, the passing rate of 8.0mm sieve is 90-100%, the passing rate of 4.75mm sieve is 30-100%, the passing rate of 2.36mm sieve is 20-50%, and the passing rate of 0.075mm sieve is 3-13%.

3. The anti-skid finish for cold-laid pavement according to claim 1, characterized in that: The high-permeability and high-viscosity adhesive is a solvent-based low-viscosity black liquid containing a polymer elastomer and a tackifying resin, with a rotational viscosity of 25°C ≤ 100mPa·s, an evaporation residue softening point ≥ 85°C, and a needle penetration of 10-300.1mm at 25°C.

4. The anti-skid finish for cold-laid pavement according to claim 1, characterized in that: The performance indexes of the anti-slip fine coating after molding are as follows: The pendulum friction coefficient BPN ≥ 70, and BPN ≥ 65 one year after opening to traffic; Transverse force coefficient SFC ≥ 54, structural depth TD ≥ 0.6mm; Water permeability coefficient ≤120ml / min, wet wheel abrasion value 6d ≤800g / m².

5. The anti-skid finish for cold-laid pavement according to claim 1, characterized in that: The fiber is glass fiber, has an alkali metal oxide content of ≤0.8%, a breaking strength of ≥0.25N / tex, and needs to be evenly dispersed in the mixture without agglomeration.

6. The anti-skid finish for cold-laid pavement according to claim 1, characterized in that: The cement is 32.5 or 42.5 grade Portland cement.

7. The anti-skid finish for cold-laid pavement according to claim 1, characterized in that: The surface quality requirements of the anti-slip fine cover are: the surface is flat and dense, without exposed rough materials and protrusions, the flatness is ≤3mm, the driving noise is ≤70dB, which is close to the effect of hot-laid ultra-thin cover.

8. A method for applying an anti-slip finish according to any one of claims 1 to 7, characterized in that: The following steps are involved: Pretreatment: If the width of cracks on old pavement is ≤5mm, they should be treated directly; if the width of cracks on old pavement is ≥5mm, they should be filled; if the depth of ruts is ≤15mm, they should be covered directly; if the depth of ruts is >15mm, they should be filled first; if the gaps in cement pavement are grouted, fine milling and leveling should be carried out; Spread the adhesive layer: Use a special spreading vehicle to evenly spray the high-permeability and high-viscosity adhesive, and cure it until the wheel does not stick to it for ≤1 hour; Paving mixture: Slurry sealer mixes aggregate, emulsified asphalt, water, cement, and fiber at room temperature, with a paving thickness of 6-10mm and a speed of 10-30m / min; Health preservation opening: Traffic will be opened after 1-2 hours of health preservation. When the temperature is ≥5℃, the health preservation time will be extended to 2 hours.

9. The anti-slip finishing method according to claim 8, characterized in that: The construction temperature control meets the following requirements: paving temperature ≥ 5℃, and temperature during the curing period ≥ 10℃.

10. The anti-slip finishing method according to claim 8, characterized in that: The rubber wheel rolling process is: After curing for 30-60 minutes, the rubber-wheel roller rolls the road surface 2-3 times at a speed of 1.5-2.0 km / h, first rolling the sides of the road surface and then the middle of the road surface.